The francophone occidental africa between the cfa franc and the economical and social development project since 1960 - (:unkn) unknown (My University, 2023)
This thesis is based on the contemporary history of French-speaking West Africa. Its anchor point is the theme of the CFA franc (Franc of the French Community of Africa for West Africa, and Franc of the French Cooperation in Africa for Central Africa) and the project of economic and social development since 1960. The research is based on a multidisciplinary approach. It analyses trade and economic policy issues that are constantly being debated at the international level. The problematic concerns the role of currency in international relations: the case of the CFA franc between France and its former colonies in sub-Saharan Africa. Indeed, independence implies, above all, political, economic and social sovereignty for a country. The CFA franc is a topical issue that fascinates many people. In the 21st century, the CFA franc remains the only colonial currency still used by fourteen countries, twelve of which are former French colonies. These are Benin, Burkina Faso, Central African Republic, Chad, Côte d'Ivoire, Congo, Gabon, Mali, Niger, Senegal and Togo. Equatorial Guinea (Spanish-speaking) and Guinea-Bissau (Portuguese-speaking) had joined these French-speaking countries in 1984 and 1997 respectively. Faced with the development challenges in the contemporary world, the countries using the CFA franc are among the worst pupils in this class. Apart from the high rate of impoverishment, the populations of this area are subject to the scourges of insecurity (in the Sahel and the Gulf of Guinea, for example) and emigration. My approach has enabled me to get a better understanding of the functioning of this currency in order to understand its impact on the daily lives of its users.Three methodological tools were used to carry out this study. First, documentation. This has helped me to take stock of the existing documentation. I accessed first-hand documents between 2018 and 2022. Secondly, in order to verify certain hypotheses, I conducted field surveys to
Keywords: African Research